Determining C- and P-factors of RUSLE for different land uses and management practices across agro-ecologies: case studies from the Upper Blue Nile basin, Ethiopia. (4th March 2021) - Kebede, Birhanu; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Adgo, Enyew; Ebabu, Kindiye; Meshesha, Derege Tsegaye; Tsubo, Mitsuru; Masunaga, Tsugiyuki; Fenta, Ayele Almaw
ABSTRACT: Cover and management (C) and support practice (P) are the most dynamic factors of the Revised Universal Soil Loss Equation- a widely used model to estimate mean annual soil loss. The aim of this study was, therefore, to determine C - and P -factors for four land management practices and three land use types in three agro-ecologies: Guder (highland), Aba Gerima (midland), and Dibatie (lowland) through selecting a rainfall erosivity (R)-factor model. We collected two seasons' daily soil loss data from 42 runoff plots. Compared to the control, the P -factor in cropland ranged from 0.15 to 0.53 for soil bund, 0.18 to 0.5 for fanya juu, and 0.06 to 0.44 for soil bund with grass; and in non-cropland plots from 0.03 to 0.42 for trench with exclosure. The C -factor ranged from 0.004 for teff to 0.64 for chili pepper in crop land; and from 0.001 in degraded bushland to 0.49 in grassland for non-cropland. Overall, the average P- values decreased in the order midland > highland > lowland for cropland plots and highland > lowland > midland for non-cropland plots. Accurate determination of C - and P - factor values for the local conditions helps greatly improve soil loss prediction in this basin and other similar regions.